2006
DOI: 10.1007/s00125-006-0253-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-conditioned medium inhibits the differentiation of 3T3-L1 and human abdominal preadipocytes

Abstract: Aims/hypothesis: In obesity, a limited adipogenic capacity may promote adipocyte hypertrophy and increase the risk of insulin resistance and type 2 diabetes. Recent data indicate that macrophages reside within adipose tissue in obese rodents and humans. We hypothesised that secreted macrophage factors may inhibit adipogenesis.Materials and methods: Conditioned media from cultured murine J774 or human THP-1 macrophages were collected, and added to either murine 3T3-L1 preadipocytes or human abdominal stromal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 39 publications
7
72
0
Order By: Relevance
“…2E and 2F). Inhibitory effects of macrophage factors on insulin sensitivity were also observed in 3T3-L1 and human primary preadipocytes (Constant et al, 2006) demonstrating that our model system is well suitable for studying the effects of macrophage-secreted factors on fat cell function.…”
Section: Macrophage-secreted Factors Inhibit Insulin-dependent Procesmentioning
confidence: 54%
“…2E and 2F). Inhibitory effects of macrophage factors on insulin sensitivity were also observed in 3T3-L1 and human primary preadipocytes (Constant et al, 2006) demonstrating that our model system is well suitable for studying the effects of macrophage-secreted factors on fat cell function.…”
Section: Macrophage-secreted Factors Inhibit Insulin-dependent Procesmentioning
confidence: 54%
“…Conditioned medium was prepared as described previously (Constant et al 2006). Briefly, cells were resuspended at a density of 1!10 6 cells/ml in THP-1 growth medium and differentiated into macrophages with the addition of 100 nM phorbol 12-myristate 13-acetate (PMA; Sigma-Aldrich) for 24 h. The medium was replaced with serum-free THP-1 growth medium (without PMA), and conditioned by THP-1 macrophages for 24 h. The conditioned medium (THP-1-MacCM) was collected and centrifuged at 150 g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Hypertrophied adipocytes display upregulated inflammatory gene expression and decreased responsiveness to insulin, leading to inappropriate lipolysis and the deleterious deposition of fatty acids in the liver and muscle (Danforth 2000, Heilbronn et al 2004, Arner et al 2010. A number of studies have demonstrated that macrophages can release factors that impair adipogenesis (Constant et al 2006becomes active as an inflammatory cytokine when processed by caspase 1 within the inflammasome, as recently reviewed (Tack et al 2012). IL1b expression is increased in obese mouse models, and it is associated with metabolic inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophagesecreted factors are known to block adipogenesis and insulin action in adipocytes and hepatocytes by the downregulation of insulin receptor sustrate-1 (IRS-1), leading to decreased AKT phosphorylation. [1][2][3][4] The mechanisms through which pro-inflammatory cytokines, like tumor necrosis factor-a, interleukin-6 (IL-6) and IL-1b interact with cellular insulin signal transduction cascades have been described in the last years. [5][6][7][8][9] Lactoferrin is a pleiotropic glycoprotein (80 kDa) and a prominent component of the first line of mammalian host defense, acting on specific lactoferrin receptors that exist in a variety of cells, like monocytes, lymphocytes, adipocytes, hepatocytes and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%